The Genetics of Non-conventional Wine Yeasts: Current Knowledge and Future Challenges - Masneuf-Pomarede, Isabelle; Bely, Marina; Marullo, Philippe; Albertin, Warren (Frontiers in Microbiology, 2016)
Saccharomyces cerevisiae is by far the most widely used yeast in oenology. However, during the last decade, several other yeasts species has been purposed for winemaking as they could positively impact wine quality. Some of these non-conventional yeasts (Torulaspora delbrueckii, Metschnikowia pulcherrima, Pichia kluyveri, Lachancea thermotolerans, etc.) are now proposed as starters culture for winemakers in mixed fermentation with S. cerevisiae, and several others are the subject of various studies (Hanseniaspora uvarum, Starmerella bacillaris, etc.). Along with their biotechnological use, the knowledge of these non-conventional yeasts greatly increased these last 10 years. The aim of this review is to describe the last updates and the current state-of-art of the genetics of non-conventional yeasts (including S. uvarum, T. delbrueckii, S. bacillaris, etc.). We describe how genomics and genetics tools provide new data into the population structure and biodiversity of non-conventional yeasts in winemaking environments. Future challenges will lie on the development of selection programs and/or genetic improvement of these non-conventional species. We discuss how genetics, genomics and the advances in next-generation sequencing will help the wine industry to develop the biotechnological use of non-conventional yeasts to improve the quality and differentiation of wines.